COASTAL AND SEAFLOOR SANDY AND GRAVELLY SEDIMENTS OF NORTHERN LOMBOK ISLAND AND ITS POTENTIAL AS CONSTRUCTION MATERIALS - HANANTO KURNIO (Indonesian Mining Journal, 2006)
Based on grain size analyses as well as microscopic and megascopic observations, coastal and seafloor sediments of northern Lombok Island are subdivided into 6 units : slightly gravely sand, slightly gravelly muddy sand, sand, gravelly sand, silty sand and slightly gravelly sandy mud. The slightly gravelly sand, sand and gravelly sand are of interest for its potentiality for construction material due to its widespread distribution and its low content of muddy and silty materials. Some offshore sediments are possibly landslide in origin as observed from factors such as steep seabottom slope of northern Lombok, graphic presentations of bimodal - polymodal histogram presentations as well as poorly sorted character of frequency curve diagrams and evidence from analog seismic record which demonstrates slumping of seabottom sediments.